Using the Kulldorf’s Scan Statistics to Identify Clusters of Tuberculosis Incidence in Muaro Jambi Regency Indonesia - Muhammad Syukri; Rizalia Wardiah (GLOBAL HEALTH SCIENCE GROUP, 2023)
There was a significant increase in tuberculosis cases from 2016 to 2019 in Muaro Jambi Regency. Many studies on TB risk factors have been carried out, but spatial cluster analysis has never been carried out in Muaro Jambi Regency. This study aimed to identify the spatial clusters of TB in Muaro Jambi Regency in 2020 using the statistical Kulldorf's scan method. Data on all TB cases at sub-district level in 2020 were obtained from the Integrated Tuberculosis Information System (SITB) of the Jambi Provincial Health Office. Sub-district office coordinate data were obtained with the help of the Google Earth Pro application. Data were analyzed using Kulldorf’s poisson spatial scan statistics based on population data and monthly number of TB cases using the free application SaTScan 10.0. Statistical scan spatial analysis found one most likely to cluster and two secondary clusters. The most likely cluster occurs in Jambi Kecil Sub-district. The first secondary cluster was found in Kasang Pudak Sub-district, and the second secondary cluster was found in Sembubuk Sub-district. The results of this study are expected to assist policy makers in increasing efforts to control and prevent TB cases by focusing on high-risk areas.